Science and Technology Governance and Ethics A Global Perspective from Europe, India and China - Ladikas, Miltos; Chaturvedi, Sachin; Zhao, Yandong; Stemerding, Dirk (Springer Nature, 2015)
R & D/Technology Policy; Ethics; Food Science; Nanotechnology; Biotechnology